THU0073 DAS28-CRP and DAS28-ESR Cutoffs for High Disease Activity in Rheumatoid Arthritis Are Not Interchangeable. (15th July 2016) - Fleischmann, R.M.; van der Heijde, D.; Gardiner, P.V.; Szumski, A.; Marshall, L.; Bananis, E.
Abstract : Background: Rheumatoid arthritis (RA) clinical trials have shown that mean DAS28 calculated using C-reactive protein (CRP) is lower than DAS28 calculated using erythrocyte sedimentation rate (ESR). We demonstrated that DAS28-CRP cutoffs equivalent to DAS28-ESR for remission and low disease activity (LDA) were 2.4 and 2.9, respectively, rather than 2.6 and 3.2. 1 Use of DAS28-ESR cutoffs to assess high disease activity (HDA) using DAS28-CRP likely underestimates the number of patients with HDA, although these values are often used interchangeably in clinical trials, and by payers and health organizations, probably excluding patients who should be eligible for advanced therapies. Objectives: To analyze baseline (BL) data from 2 etanercept (ETN) clinical trials to determine the DAS28-CRP cutoff corresponding to the validated DAS28-ESR cutoff for HDA in RA. Methods: Data were pooled from COMET and PRIZE, clinical studies in early moderate to severe RA. Descriptive statistics for DAS28-CRP and DAS28-ESR were determined for each treatment: weekly ETN 50 mg + methotrexate (MTX) or MTX only. DAS28-CRP and DAS28-ESR were compared according to the DAS28-ESR cutoff point for HDA (>5.1) using sensitivity, specificity, kappa coefficients, and proportion of discordance. Based on the DAS28-ESR cutoff, the corresponding DAS28-CRP cutoff was determined for each study and treatment group using cumulative distribution plots, receiver operator curves, and maximum concordance. These DAS28-CRP cutoffs were averaged for each study and treatment, then averaged overall. This produced the DAS28-CRP HDA cutoff corresponding best to the DAS28-ESR HDA cutoff. Results: At BL, fewer patients met the value of >5.1 by DAS28-CRP than by DAS28-ESR (table). DAS28-CRP >5.1 and DAS28-ESR >5.1 had modest agreement (kappa coefficients of 0.45 and 0.53), with high sensitivity but low specificity. In the ETN+MTX group (N=571), mean (95% CI) DAS28-CRP and DAS28-ESR were 5.7 (5.6, 5.8) and 6.2 (6.2, 6.3), respectively, with a difference of 0.6 (0.5, 0.6). In the MTX group (N=262), mean (95% CI) DAS28-CRP and DAS28-ESR were 6.0 (5.9, 6.1) and 6.5 (6.4, 6.6), respectively, with a difference of 0.5 (0.5, 0.6). We determined that DAS28-CRP of 4.6 was similar to DAS28-ESR of 5.1. Conclusions: More patients met the HDA cutoff according to DAS28-ESR than DAS28-CRP, and mean values for DAS28-CRP were lower, suggesting that use of the DAS28-ESR cutoff for DAS28-CRP for HDA underestimates disease activity. Use of the new HDA cutoff of >4.6 for DAS28-CRP, and the new DAS28-CRP cutoffs of ≤2.9 for LDA and <2.4 for remission will enable more accurate measurement of disease activity when DAS28-CRP is used. 1 References: Fleischmann R, et al. Ann Rheum Dis. 2015;74:1132–7. Disclosure of Interest: R. Fleischmann Consultant for: Pfizer, D. van der Heijde Consultant for: AbbVie, Amgen, Astellas, AstraZeneca, BMS, Celgene, Daiichi, Eli-Lilly, Galapagos, Janssen, Merck, Novartis, Pfizer, Roche, Sanofi-Aventis, UCB, Employee of: Director of Imaging Rheumatology bv, P. Gardiner: None declared, A. Szumski Employee of: inVentiv Health, L. Marshall Shareholder of: Pfizer, Employee of: Pfizer, E. Bananis Shareholder of: Pfizer, Employee of: Pfizer